2022
DOI: 10.1038/s41560-022-01057-y
|View full text |Cite
|
Sign up to set email alerts
|

Energy demand reduction options for meeting national zero-emission targets in the United Kingdom

Abstract: In recent years, global studies have attempted to understand the contribution that energy demand reduction could make to climate mitigation efforts. Here we develop a bottom-up, whole-system framework that comprehensively estimates the potential for energy demand reduction at a country level. Replicable for other countries, our framework is applied to the case of the United Kingdom where we find that reductions in energy demand of 52% by 2050 compared with 2020 levels are possible without compromising on citiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 24 publications
2
44
0
Order By: Relevance
“…In recent years, low energy demand scenarios have been proposed as alternative mitigation pathways [1,2]. These have been developed in response to both the inadequate pace of carbon mitigation to date [3] and the heavy reliance of 2-degree-consistent climate scenarios on negative emission technologies; technologies suggested to be infeasible at large scale [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, low energy demand scenarios have been proposed as alternative mitigation pathways [1,2]. These have been developed in response to both the inadequate pace of carbon mitigation to date [3] and the heavy reliance of 2-degree-consistent climate scenarios on negative emission technologies; technologies suggested to be infeasible at large scale [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…A low energy demand scenario developed as part of the Positive Low Energy Futures work in the UK has suggested a ~50 % reduction in energy demand is possible while improving social outcomes, which compares to the essentially flat UK energy demand seen over the past 50 years [2]. Moreover, Barrett et al [2] found that at least a 40 % energy demand reduction is needed to meet the 2050 net-zero target committed to by the government, without relying upon mass deployment of unproven negative emissions technologies such as BECCS. Previous work at the global level found that a ~60 % reduction on current final energy use would be possible by 2050 while also providing decent living standards for all [10].…”
Section: Introductionmentioning
confidence: 99%
“…Debates on low-carbon transitions increasingly pay attention to questions of justice and equity [10][11][12] , highlighting important dimensions that techno-economic analyses, which have long dominated these debates, ignore 13,14 . Mapping different justice dimensions (distributive, procedural, epistemic), as others have done, is an important first step 15 .…”
mentioning
confidence: 99%
“…He advocates policy interventions to encourage more energy-e cient choices and more support for new energy-e cient technologies. Some of the rapid and large-scale changes needed in the sociotechnical systems that provide energy services are described in more detail by Barrett et al (2022), who report a UK modelling case study that, by utilising the full potential for improvements, reduces energy demand by 2050 by 52% compared to that of 2020. If such demand reductions could be achieved across similar energy economies, it would be much easier to meet global climate goals for carbon dioxide emissions.…”
mentioning
confidence: 99%